Implementation Strategy of Digital Marketing Tourism Bus Rental Satisfaction in the New Era of Normality - Savitri, Shela Indah; Kharisma, Indri; Hadistia, Ananda (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
Purpose of study to find out and describe the attitudes and responses of businessman regarding the PO Juragan 99 tourism bus rental business in the new era of normality, to find out and describe the related digital marketing strategies in the PO Juragan 99 tourism bus rental and to find out and describe the extent of the implications of the digital marketing strategy on bus rental PO Juragan 99 in the new era of normality to achieve customer satisfaction This study uses a qualitative method. The qualitative method by Miles which consists of three streams of activity occurring simultaneously, which includes data reduction, data presentation, and drawing conclusions or verification used in this study. Primary data is the main data or base used in this reasearch. The main data obtained from this research is primary data because it is directly from the respondent's data. Data taken from interviews, observation and documentation. Data analysis was performed using 4 (four) stages, namely data collection, data reduction, data presentation and conclusion drawing. The output produced in this study is a journal. Theoretically, the results of this research will add to the repertoire of knowledge, especially in the field of developing digital marketing strategies for businessman.